NEW ASPECTS OF THE LIFE AND ACTIVITIES OF THE DEPUTY PRIME MINISTER OF THE TURKESTAN AUTONOMY ISLAM SHOAKHMEDOV (Scientific journal of the Fergana State University, 2023)
The article provides information about the life and work of the Deputy Prime Minister of the Turkestan Autonomous Region, lawyer, political journalist Islam Shohsultonovich Shoahmedov (1186-1922).In addition, new aspects of the Jadid political leader and the establishment of the Muslim newspaper and his activities as a major publisher, as well as his activities and views as a political correspondent, are covered in the works and periodicals of local and foreign scholars.The life and work of Islam Shohsultonovich Shoahmedov have always been in the spotlight of local and foreign scholars. Their research focused on Islam Shoahmedov's activities as a modern enlightener, his publishing activities, and his activities as Deputy Prime Minister of the Turkestan Autonomous Region. However, in some studies by Soviet scholars, the autonomy of Turkestan and the activities of the Jadids were viewed as bourgeois-nationalist.